BEGONIA SINUATA MEISN., A NEW RECORD FOR INDONESIA - Deden Girmansyah (PTTI, 2014)
An unidentified Begonia from Karimunjawa and Bangka, Indonesia has been identified as Begonia sinuata Meisn., a Mainland Asian taxon based on habit, leaf shape (cordate leaf base, entire leaf margin, leaf surface with star-like hairs on both side) and three unequal wings. The largest wings 10–16 mm wide.